Macroeconomic Drivers of ROA in Indonesian Islamic Commercial Banks: A Time Series Analysis (2019-2024) - Anggun Milania Vio M; Khusnudin Khusnudin (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
This study examines the impact of the BI Rate, inflation, and the rupiah exchange rate on the profitability of Islamic Commercial Banks in Indonesia during 2019–2024. Previous studies on Islamic bank profitability have produced inconsistent findings due to differences in research periods, data structures, and analytical approaches. Most prior studies relied on annual or panel data, limiting their ability to capture short-run macroeconomic dynamics during the post-pandemic recovery period and monetary policy tightening. This study addresses these gaps by employing monthly time-series data and the Error Correction Model (ECM) framework to analyze both short-run and long-run relationships within the Monetary Transmission Mechanism (MTM) perspective. Secondary data were obtained from Bank Indonesia, the Financial Services Authority (OJK), and Statistics Indonesia (BPS), comprising 72 monthly observations from January 2019 to December 2024. The findings reveal that, in the long run, the BI Rate negatively and significantly affects Return on Assets (ROA), while inflation and the exchange rate positively and significantly influence profitability. In the short run, macroeconomic variables do not significantly affect ROA, indicating that Islamic bank profitability is relatively resilient to temporary macroeconomic shocks. However, the significant Error Correction Term (ECT) confirms the existence of a long-run adjustment mechanism toward equilibrium. This study aims to fill the gap in knowledge about banking and provide new perspectives for policymakers, especially central banks, managers, and stakeholders. By focusing on macroeconomic factors that influence profitability.